Reliable template protection technique for biometric authentication - Ong, Teng Sian; Teoh, Andrew Beng Jin; Khor, S. E.; Tee, Connie (The Institute of Electronics, Information and Communication Engineers, 2008)
This paper proposes a biometric template protection technique using Dynamic Quantization Transformation to convert biometrics into template of bitstring. The proposed method enables the authentication to take place in the transformed domain rather than original biometric feature space. We outline four requirements for a reliable template protection in the realm of fingerprint system. Several security and experimental analysis have been conducted to show the technique is feasible in practice.